The effects of prostaglandin E2 on gonadal development and germ cell proliferation, and its presence during the gonadal cycle in the sea cucumber, Holothuria scabra - Nontunha N. (2023)
Prostaglandin E2 (PGE2) plays important roles in several physiological processes, including reproduction of several marine invertebrate species. The aims of the present study were to characterize the putative prostaglandin E synthase (PGES), an enzyme that is involved in the PGE2 biosynthetic pathway, in the sea cucumber, H. scabra. We then examined the presence and distribution of PGES and PGE2 in gonadal tissues using RT-qPCR and immunohistochemistry, and further investigated the effects of PGE2 on gonadal development and germ cell proliferation by using functional assays. Transcriptomic data and molecular cloning analyses from gonadal tissues of H. scabra were performed, and these tissues were found to have the PGES in H. scabra, namely Hs-cPGES3. By using RT-qPCR, the Hs-cPGES3 mRNA expression levels were higher at the early stages than the late stages of the gonadal cycle. In addition, the presence of PGE2 and its corresponding enzyme, Hs-cPGES3, was detected in the gonads with the highest intensities appearing in gamete cytoplasm during the early stages than those at the late stages. Functionally, PGE2, at the doses of 50 and 500 ng/g BW, significantly promoted gonadal development, gonado-somatic index (GSI), gonadal tube diameters, and increased germ cell proliferation, compared with those of the control animals (P < 0.05). Taken together, our findings are the first to demonstrate the presence of PGE2 and its biosynthetic-associated enzymes in the gonadal tissues, and its effects on gonadal development and germ cell proliferation in this sea cucumber. The knowledge gained would improve understanding of PGE2 mechanism in controlling gonadal development, which could be useful in enhancing the production of seeds for aquaculture of H. scabra.